2004
DOI: 10.1143/jjap.44.l85
|View full text |Cite
|
Sign up to set email alerts
|

Laser Speckle Microscope for Instantaneous Determination of Condition of Single Living Cell

Abstract: amplifier and scaling equipment. The lirni will undertake the entire analysis if desired.An alternativc analysis, from foils consisting of neptunium, plutonium, and z3xU in boron shields, of bare and cadmium covered gold. and of sulphur, is available for monitoring nuclear reactor excursions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…When the observation region in the leaf was changed, it was found that the laser speckle fluctuation on an edge of the leaf was more active than any other regions of the leaf and that the condition of the observed laser speckle on a living leaf was slightly different from that on human cells. [1][2][3] The images obtained by the laser speckle microscopy consist of static speckles and dynamic speckles which cause speckle fluctuations. 1,2,4) In this experiment, the static speckle came to the front and the dynamic speckle was posteriorly-located, while the dynamic speckle was mainly observed in the case of human cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When the observation region in the leaf was changed, it was found that the laser speckle fluctuation on an edge of the leaf was more active than any other regions of the leaf and that the condition of the observed laser speckle on a living leaf was slightly different from that on human cells. [1][2][3] The images obtained by the laser speckle microscopy consist of static speckles and dynamic speckles which cause speckle fluctuations. 1,2,4) In this experiment, the static speckle came to the front and the dynamic speckle was posteriorly-located, while the dynamic speckle was mainly observed in the case of human cells.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] The images obtained by the laser speckle microscopy consist of static speckles and dynamic speckles which cause speckle fluctuations. 1,2,4) In this experiment, the static speckle came to the front and the dynamic speckle was posteriorly-located, while the dynamic speckle was mainly observed in the case of human cells. 5) This may be explained by the different cellular structure between plants and human or animals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to MM-OCT and light microscopy, we use laser speckle reflectometry as a 2-D reference modality to investigate sample motion. 21 To that, the sample was illuminated in a darkfield manner by a collimated laser beam at 638 nm, which was generated by a fiber-coupled laser diode with 1 mW output power (Lasiris PTL-500-635-1-2.0, Coherent Canada) and a fiber collimator (Fig. 2).…”
Section: Light Microscopy and Laser Speckle Reflectometrymentioning
confidence: 99%